Cadmium mapping and contamination potential on different paddy field managements in Sragen Regency, Indonesia - Pungky Ferina; M M A Retno Rosariastuti; Widyatmansi Sih Dewi (Journal of Degraded and Mining Lands Management, 2020)
Cadmium (Cd) is a harmful metal for paddy soil that is affected by inorganic fertilizer, pesticides, and industrialization. This study aimed to investigate the Cd contents in paddy soil, plant tissue, and grain, as well as the spatial distribution of potential Cd contamination. This study was conducted in Sragen Regency on paddy fields with different management, i.e., organic paddy fields, conventional paddy fields (Alfisols, Entisols, Inceptisols, and Vertisols), and paddy fields that often use wastewater (textiles, batik, and sugar factories) for irrigation. Forest land was used as a control. This study used descriptive explorative methods based on overlay land use, soil type, and industrial distribution map of Sragen Regency. The results showed that paddy soils with different management had higher Cd content than the forest soil. Organic paddy field had the lowest Cd content in soil (0.019 ppm) and rice grain (0.0006 ppm). Approximately 1,914.4 ha (3%) of paddy field in Sragen Regency that uses sugarcane industry wastewater as irrigation had the highest soil Cd content (0.16 ppm). In contrast, the highest Cd content in rice grain (0.046 ppm) was observed in conventional paddy field. The management of paddy field and rice cultivation significantly affected Cd contamination in soil and rice grain; therefore, environmentally friendly paddy field management needs to be encouraged.